﻿Sarcoidosis on tattoos: a review of the literature from 1939 to 2011 - Kluger, N. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2013)
Sarcoidosis is an autoimmune disease of unknown etiology characterized by the presence of non-caseating epithelioid cell granulomas in multiple organs. Cutaneous sarcoidosis occurs in approximately 25% of the cases. Sarcoid reactions on old scars, traumatized skin sites and around embedded foreign material have long been observed. For the past 70 years, sarcoidal granulomas on tattoos and permanent make-up have also been documented. Granulomatous and sarcoidal tattoo reactions may be the first and sometimes only cutaneous manifestation of systemic sarcoidosis. This review summarizes the currently available data on this topic and discusses the issues related to the diagnosis, management and physiopathogeny of sarcoidal reactions on tattoos.